High-Temperature Performance and Multiscale Damage Mechanisms of Hollow Cellulose Fiber-Reinforced Concrete - Liping Guo; Wenxiao Zhang; Wei Sun; Bo Chen; Yafan Liu (Advances in Materials Science and Engineering)
Spalling resistance properties and their damage mechanisms under high temperatures are studied in hollow cellulose fiber-reinforced concrete (CFRC) used in tunnel structures. Measurements of mass loss, relative dynamic elastic modulus, compressive strength, and splitting tensile strength of CFRC held under high temperatures (300, 600, 800, and 1050°C) for periods of 2.5, 4, and 5.5 h were carried out. The damage mechanism was analyzed using scanning electron microscopy, mercury intrusion porosimetry, thermal analysis, and X-ray diffraction phase analysis. The results demonstrate that cellulose fiber can reduce the performance loss of concrete at high temperatures; the effect of holding time on the performance is more noticeable below 600°C. After exposure to high temperatures, the performance of ordinary concrete deteriorates faster and spalls at 700–800°C; in contrast, cellulose fiber melts at a higher temperature, leaving a series of channels in the matrix that facilitate the release of the steam pressure inside the CFRC. Hollow cellulose fibers can thereby slow the damage caused by internal stress and improve the spalling resistance of concrete under high temperatures.